2012
DOI: 10.1097/mpa.0b013e31823cd873
|View full text |Cite
|
Sign up to set email alerts
|

Screening of R122H and N29I Mutations in the PRSS1 Gene and N34S Mutation in the SPINK1 Gene in Mexican Pediatric Patients With Acute and Recurrent Pancreatitis

Abstract: Patients bearing the N34S G allele exhibited a 10-fold increased risk of developing AP compared with controls, suggesting that the SPINK1 N34S mutation represents an etiologic risk factor for AP in our Mexican pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
3
9
0
5
Order By: Relevance
“…Homozygous SPINK1 mutation predisposes to severe acute pancreatitis and runs a subsequent risk of developing chronic pancreatitis that has not been shown before. The only study in children with acute pancreatitis from Mexico [20] showed genetic mutations in 4 (3 SPINK1, 1 PRSS1) of 58 patients and none in controls. All these four children with mutations had one or more known etiological factors associated with pancreatitis.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Homozygous SPINK1 mutation predisposes to severe acute pancreatitis and runs a subsequent risk of developing chronic pancreatitis that has not been shown before. The only study in children with acute pancreatitis from Mexico [20] showed genetic mutations in 4 (3 SPINK1, 1 PRSS1) of 58 patients and none in controls. All these four children with mutations had one or more known etiological factors associated with pancreatitis.…”
Section: Discussionmentioning
confidence: 90%
“…Studies in adults have shown that 25-44% of idiopathic chronic pancreatitis cases are associated with genetic mutations (mainly SPINK1) [13][14][15][16]. So far, there are three studies in chronic/acute recurrent pancreatitis in children [17][18][19] and only one in acute pancreatitis of various aetiologies [20]. Unlike in adults, there is a scarcity of studies on idiopathic pancreatitis in children and none so far on the impact of genetic mutations of natural history of acute and acute recurrent pancreatitis.…”
Section: Introductionmentioning
confidence: 97%
“…In a pediatric series of 92 children with AP and RP attended at the Hospital of Pediatría (Guadalajara, México), we identified mutations (R122H and N34S) in a group of AP exclusively; this represented a 13-fold increased risk of having AP compared with the general population in which we did not identified these mutations. The SPINK1 N34S mutation was identified in 3/58 cases with AP, none in the group of RP nor in general population and it was found that the cases bearing the SPINK1 N34S G allele exhibited a 10-fold increased risk of developing AP compared with the general population, suggesting that the SPINK1 N34S mutation represents an etiological risk factor for the development of AP in our pediatric patients (25).…”
Section: Definitionmentioning
confidence: 94%
“…The family history of pancreatitis is an important etiological factor that has to be asked, since hereditary pancreatitis may be defined as two patients with history of pancreatitis within one generation or more than two patients in more than one generation (20). In 7.2 to 37.6% of children with acute pancreatitis, no etiological factors are identified and these cases are classified as idiopathic (3)(4)(5)9,10,14,(21)(22)(23)(24)(25). Another issue regarding etiology is the genetics of pancreatic disease.…”
Section: Definitionmentioning
confidence: 99%
“…The pancreatic protease/anti-protease system and inflammatory cytokines play pivotal roles in the pathogenesis of AP [5]; hence, most previous studies have mainly focused on polymorphisms occurring in genes related to these systems [6][9]. It has been reported that the anti-inflammatory response also plays an important role in AP, but limited studies have investigated the relationship between polymorphisms in genes encoding anti-inflammatory molecules and AP.…”
Section: Introductionmentioning
confidence: 99%